2012
DOI: 10.1128/ec.00069-12
|View full text |Cite
|
Sign up to set email alerts
|

NsdC and NsdD Affect Aspergillus flavus Morphogenesis and Aflatoxin Production

Abstract: The transcription factors NsdC and NsdD are required for sexual development in Aspergillus nidulans. We now show these proteins also play a role in asexual development in the agriculturally important aflatoxin (AF)-producing fungus Aspergillus flavus. We found that both NsdC and NsdD are required for production of asexual sclerotia, normal aflatoxin biosynthesis, and conidiophore development. Conidiophores in nsdC and nsdD deletion mutants had shortened stipes and altered conidial heads compared to those of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
104
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 44 publications
7
104
1
1
Order By: Relevance
“…However, previous studies also have suggested that NsdD might be a potential repressor of conidiation (Han et al 2001;Cary et al 2012). For instance, overexpression of nsdD resulted in the near total absence of conidiation with formation of elongated aerial hyphae.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, previous studies also have suggested that NsdD might be a potential repressor of conidiation (Han et al 2001;Cary et al 2012). For instance, overexpression of nsdD resulted in the near total absence of conidiation with formation of elongated aerial hyphae.…”
Section: Discussionmentioning
confidence: 96%
“…However, as enhanced expression of nsdD also resulted in elevated sexual development even under unfavorable conditions for sexual fruiting, it has been hypothesized that NsdD primarily functions in positively regulating sexual development rather than repressing conidiation. Additional studies in A. flavus demonstrated that the removal of nsdD resulted in elevated expression of brlA (Cary et al 2012). They found that both NsdC [another sexual activator and NsdD are required for production of asexual sclerotia, normal aflatoxin biosynthesis, and conidiophore development.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to VeA, NsdC modulation could participate to the morphological modifications observed in hyssop-treated cultures (Figure 3). It has also been linked to aflatoxin cluster-gene expression [51] as well as being a global regulator of secondary metabolism [52]. More data is yet to be collected on the individual and possibly collaborative roles of both of these factors in the regulation of secondary metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Such experiments include a bottom-up approach where specific genes are targeted for disruption or ectopic expression and the resulting effect on transcriptional regulation or biological processes is determined [26][27][28][29] . Other common approaches include the use of chemical treatment, environmental conditioning, host-pathogen interaction or other stimuli relevant to the investigation to identify novel genes, proteins, interactions, expression profiles, and entire processes responding to the stimuli [30][31][32][33] .…”
Section: Functional Genomics and Secondary Metabolismmentioning
confidence: 99%
“…Another global regulatory gene, nsdC, mainly known for its role in development in A. nidulans 91) , was also shown to be required for AF production in A. flavus 27) . In addition to loss of AF biosynthesis, A. flavus ΔnsdC mutants also demonstrated reduced aflatrem content compared to a control strain.…”
Section: -1 Global Regulationmentioning
confidence: 99%